1996
DOI: 10.1007/bf00218833
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary tyrosinemia type 1: novel missense, nonsense and splice consensus mutations in the human fumarylacetoacetate hydrolase gene; variability of the genotype-phenotype relationship

Abstract: The complete fumarylacetoacetate hydrolase (FAH) genotype of probands of thirteen unrelated families with hereditary tyrosinemia type 1 (HT 1) was established. The screening was performed by analysis of exons 2-14 of the FAH gene by using the polymerase chain reaction (PCR) and of the mRNA by reverse transcription/PCR. Nine different mutations were identified, of which six are novel. Three mutations involve consensus sequences for correct splicing, viz. IVS 6-1 (g-t), IVS 7-1 (g-a) and IVS 12 + 5 (g-a). Two mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…The Iranian child with a compound clinical phenotype of dextrocardia and HT1, is a heterozygous with this mutation. Therefore, he presented with a chronic progression and slightly increased succinylacetone in the blood, compared to the acute form of HT1 with R237X homozygous reported previously [3,8]. The result of this study has application in patient screening and genetic counseling.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The Iranian child with a compound clinical phenotype of dextrocardia and HT1, is a heterozygous with this mutation. Therefore, he presented with a chronic progression and slightly increased succinylacetone in the blood, compared to the acute form of HT1 with R237X homozygous reported previously [3,8]. The result of this study has application in patient screening and genetic counseling.…”
Section: Discussionsupporting
confidence: 51%
“…The mutation of R237X was first reported in a Turkish proband with HT1. This proband carried the homozygous R237X mutation [8]. Another nine forms of HT1 patient coming from different families in Saudi Arabia were also detected with the homozygous R237X mutations [9].…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, recent studies have demonstrated that sequences not located at the intron/exon borders, regulate the RNA splicing process. 28 These include several silent exonic polymorphisms [29][30][31][32][33] which do not confer an amino acid change.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is common among patients of French Canadian origin and was also reported in 45% of the West European patients (Grompe et al, 1994, Ploos van Amstel et al, 1996. The observation of this mutation in patient 3 whose family has resided in the same village for the past 500 years, suggests that the mutation has either occurred multiple times world wide or has originated in the Middle East.…”
Section: Resultsmentioning
confidence: 76%